Analysis of the Efficiency of the Management of Zakat, Infaq, and Sadaqah Funds at BAZNAS SU - Zainul Fuad; Yenni Samri Juliati Nasution; Halimatussakdiyah Halimatussakdiyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to find out the level of efficiency of Zakat, Infaq and Shodaqoh (ZIS) management at BAZNAS SU. This research is quantitative descriptive. The data used to measure the level of efficiency is the financial reports of BAZNAS SU in 2017-2020 by using the Data Envelopment Analysis Software (DEAP) 2.1 method with the assumption of Constant Return to Scale (CRS) using a production approach. The input variables used are operational cost, socialization cost, personnel cost and total assets. While the output variable is collected funds and channeled funds. The results shows that the level efficiency of ZIS management at BAZNAS SU in 2017-2020 has been efficient with all variables reaching 100% which means that ZIS management at BAZNAS SU has been efficient. So that it is able to use existing inputs to produce maximum output.